Anti-obesity effect and UHPLC-QTOF-MS/MS based metabolite profiling of Solanum nigrum leaf extract - Zain Ul Aabideen; Muhammad Waseem Mumtaz; Muhammad Tayyab Akhtar; Muhammad Asam Raza; Hamid Mukhtar; Ahmad Irfan; Syed Ali Raza; Muhammad Nadeem; Yee Soon Ling (Asian Pacific Journal of Tropical Biomedicine, 2022)
Objective: To evaluate the antioxidant potential and pancreatic lipase inhibitory action of optimized hydroethanolic extracts of Solanum nigrum. Methods: Optimized extraction for maximum recovery of metabolites was performed using a combination of freeze-drying and ultrasonication followed by determination of antioxidant and antiobesity properties. The ultra-high performance liquid chromatography equipped with mass spectrometry was used to analyze metabolite profiling of Solanum nigrum. Computational studies were performed using molecular docking and electrostatic potential analysis for individual compounds. The hypolipidemic potential of the most potent extract was assessed in the obese mice fed on fat rich diet. Results: The 80% hydroethanolic extract exhibited the highest extract yield, total phenolic contents, total flavonoid contents along with the strongest 2,2-diphenyl-1-picrylhydrazyl scavenging activity, total antioxidant power, and pancreatic lipase inhibitory properties. The 80% hydroethanolic extract not only regulated the lipid profile of obese mice but also restricted the weight gain in the liver, kidney, and heart. The 80% hydroethanolic extract also reduced alanine transaminase and aspartate transaminase concentrations in serum. The effects of plant extract at 300 mg/kg body weight were quite comparable with the standard drug orlistat. Conclusions: Solanum nigrum is proved as an excellent and potent source of secondary metabolites that might be responsible for obesity mitigation.